PEMBERIAN PILATES EXERCISE DANMODIFIKASI KONDISI KERJA MENURUNKAN KELUHAN SUBJEKTIF DAN MENINGKATKAN PRODUKTIVITAS KERJA PADA PEMBATIK CAP DI INDUSTRI BATIK - Ika Fitri Wulan Dhari; I Made Muliarta; Luh Made Indah Sri Handari Adiputra (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2017)
Characteristics of batik stamp is done by standing working attitude. Equipment used in the form of a work desk height is not in accordance with anthropometric causing work attitude with a bent position and in giving patterns on fabrics monotonous and repetitive. Intervention by designing the working conditions such as repair work desk, a picturesque repair work organization in the form of active rest between working time and rest periods as well as preventive measures in the form of Pilates exercise can reduce the complaints caused by work processes. This study aims to show that the administration of Pilates exercise and modification of working conditions can reduce the subjective complaints and improve productivity on a batik cap in batik industry. This Study is Experimental research, with treatment by subject design. The first phase (I) subjects treated with conventional working conditions. The second phase (II) subjects treated with application of Pilates exercise and improvement of working conditions in the form of additional altitude work desk and an active break. Among the second stage, given washing out period and adaptation. Normality test data with ShapiroWilk, paired t-test to test the significance difference variables musculoskeletal disorders, fatigue and work productivity. These results indicate that administration of Pilates exercise and modification of working conditions affect significantly (p <0.05). There was a decrease musculoskeletal 31.6%, 22.1% decrease in fatigue, and increase productivity by 34.56%. The conclusion that the application of Pilates exercise and modification of working conditions can lower subjective complaints and increase the productivity of batik cap in batik industry. So it is advisable to apply to the batik industry, to minimize complaints due process of batik work.